Cardiac autonomic dysfunction in anabolic steroid users. Issue 5 (18th January 2012) - Maior, A. S.; Carvalho, A. R.; Marques‐Neto, S. R.; Menezes, P.; Soares, P. P.; Nascimento, J. H. M.
Abstract : This study aimed to evaluate if androgenic‐anabolic steroids (AAS) abuse may induce cardiac autonomic dysfunction in recreational trained subjects. Twenty‐two men were volunteered for the study. The AAS group ( n  = 11) utilized AAS at mean dosage of 410 ± 78.6 mg/week. All of them were submitted to submaximal exercise testing using an Astrand–Rhyming protocol. Electrocardiogram (ECG) and respired gas analysis were monitored at rest, during, and post‐effort. Mean values of VO2, VCO2, and VE were higher in AAS group only at rest. The heart rate variability variables were calculated from ECG using MATLAB‐based algorithms. At rest, AAS group showed lower values of the standard deviation of R‐R intervals, the proportion of adjacent R‐R intervals differing by more than 50 ms (pNN50), the root mean square of successive differences (RMSSD), and the total, the low‐frequency (LF) and the high‐frequency (HF) spectral power, as compared to Control group. After submaximal exercise testing, pNN50, RMSSD, and HF were lower, and the LF/HF ratio was higher in AAS group when compared to control group. Thus, the use of supraphysiological doses of AAS seems to induce dysfunction in tonic cardiac autonomic regulation in recreational trained subjects.